Development of Siganid (Siganus guttatus) larvae during the transition period - Darsiani Darsiani; Mia Setiawati; Dedi Jusadi; Muhammad Agus Suprayudi; Asda Laining (Depik, 2022)
Siganid is better known as rabbit fish. In hatcheries, constraint that is still faced is the low survival, which was assumed to occur because of the timing for initial feeding is not solidly known. This research aimed to examine the best initial feeding time for siganus, based on evaluation on eyes and yolk reserves during the transition. The research was conducted from 24-29 March 2021 in IPUW Barru, South Sulawesi. Larvae were obtained from the second progeny (G2) of domesticated Siganus guttatus. Larvae were reared for 5-6 days without feeding. Evaluated parameters include eyes diameter and yolk reserves. Samples were observed with microscope and will be explained descriptively. Water quality parameters were measured, namely DO, salinity, pH and temperature. Eyes diameter at 6 Hour After Hatching (HAH) ranges between 81.5-128.9 µm, 13 HAH= 125.5-167.7 µm, 24 HAH= 138.2-213.9 µm, two days after hatching 2 Day After Hatching (DAH) = 113.6-193.1 µm, 3 DAH= 163.1-219.2 µm, 4 DAH= 190.4-212.6 µm. Yolk reserves diameter ranged between 137-194µm (6 HAH), 13 HAH= 152-191µm, 24 HAH= 94.0-185µm, 2 DAH= 75.3-99.63µm, 3 DAH= 42.33-87.58µm, 4 DAH= 38.17-55.59µm. After age 5 DAH, there are no larvae found alive (dead). Eyes developed at age 6 HAH and experienced pigmentation at age 24 HAH. Conversely, yolk reserves diameters were getting smaller since age 24 HAH and completely disappear at age 4 DAH. It indicates that eyes effectively see feeds at age 2 DAH. Therefore, initial feeding should be started. The water quality parameters measured were still in normal conditions according to the life of S. guttatus larvae. From this research, it can be concluded that eyes have been well functioned at age 2 DAH and yolk reserves was finished at age 4 DAH. Therefore, the initial feeding should be done at the age of 2 DAH.Keywords:Development, Siganus guttatus larvae,Transition